Evaluation of carbon content and humification index of soils under the application of by-products from sugarcane processing - Xavier, Alfredo Augusto Pereira; Nicolodelli, Gustavo; Tadini, Amanda Maria; Corá, José Eduardo [UNESP]; Villas-Boas, Paulino Ribeiro; Milori, Débora Marcondes Bastos Pereira (Elsevier, 2019)
The sugarcane processing generates by-product such as, sugarcane bagasse ash and filter cake and their proper disposal is of great environmental responsibility. Nowadays these by-products are being used for soil biofertilization without protocol. This study aimed to evaluate the applying these by-products to a single kind of soil in relation to the amount of carbon (C) and nitrogen (N) and stability of soil organic matter (SOM) through incubations varying the time. The bio-residues were applied to the soil at a proportional dose of 40 Mg ha− 1 and 10 times periods were defined. Elemental Analysis was used to determine C and N and Fluorescence Spectroscopy was used to evaluate the humification index (HLIFS) of the SOM. The control treatment did not show high variations of C during the experiment and its average value was less than 1.0% (m/m). The highest C values were obtained for fresh filter cake (TF), whose C content was 1.8% in the beginning of the experiment and, after 1 year, it was 1.16%, presenting an exponential decay. The C results were in the range of 1.0% to 1.2% for all the other treatments and did not present a statistically significant difference throughout the experiment. For HLIFS, it was the opposite. The lowest C values were obtained for TF, which also presented an exponential increase over the experiment, showing a fresh OM input in the beginning of the experiment and humification process over the time. For the other treatments, HLIFS had no statistically significant differences. The high levels of C for TF emphasize the importance of studies of SOM regarding the priming effect. Thus, this study indicates the need to create ordinances for the use of these by-products and guide lines for the correct management and application in the soil without any harm to the environment.
Keywords: Carbon; Environmental regulation; Filter cake; Humification index; LIFS; Sugarcane bagasse ash